Digital Transformation in Education: Exploring the Impact of AI on Student Engagement and Learning Outcomes - Mohd Zain, Aisyah binti; Abdullah, Hafiz bin (International Journal of Educational Insights and Innovations, 2025)
This study examines the impact of artificial intelligence (AI) on student engagement and learning outcomes in digitally transformed educational environments. Using a mixed-methods approach, the research analyzes quantitative data from 300+ students across 15 institutions, alongside qualitative insights from 50 educators. Results indicate that AI-enhanced tools significantly improve engagement metrics, with adaptive learning platforms increasing time-on-task by 22% and generative AI boosting participation by 15%. Learning outcomes improved notably in STEM subjects (12% higher scores) but showed minimal gains in humanities. However, challenges such as algorithmic bias, data privacy concerns, and equity gaps—particularly for students with low digital literacy—were identified. Educator interviews revealed a shift toward facilitator roles, though institutional barriers like insufficient training hindered optimal AI adoption. The study highlights the need for balanced AI integration, emphasizing ethical frameworks, teacher preparedness, and equitable access. Practical recommendations include digital literacy programs, bias audits for AI systems, and mandatory AI-pedagogy training for educators. While AI demonstrates strong potential to enhance education, its implementation must address pedagogical and ethical complexities to ensure sustainable, inclusive benefits. Future research should explore long-term effects and hybrid AI-human instructional models to refine best practices in digital education.